Benefits of LYM-X-SORB, a Highly Absorbed Structured Lipid Compound, in Children with Cystic Fibrosis and Pancreatic Insufficiency with Varying Degrees of Malabsorption (P08-125-19) - Stallings, Virginia (Curr Dev Nutr, 2019)
OBJECTIVES: The treatment of fat malabsorption and optimizing growth and nutritional status in patients with cystic fibrosis (CF) and pancreatic insufficiency (PI) is a challenge. A readily absorbable structured lipid (LYM-X-SORB™ [LXS]) improved fat absorption, growth, choline and essential fatty acid (EFA) status in children with CF and PI. Our objective in this secondary analysis is to determine if subjects with varying degrees of fat malabsorption show greater improvements with 3-month LXS treatment. METHODS: Subjects with CF and PI (5–17yrs) participated in a 12-month double-blind randomized placebo-controlled LXS trial with a 3-month interim visit. LXS and placebo had similar calorie (303 or 456 kcal/d) and fat content (11 or 18 g/d), and LXS had 7-fold greater choline; dose depended on age. CFA was assessed with 72-hour stool and 3-day weighed food records. Height, weight and BMI Z-scores were calculated. Plasma linoleic and α-linolenic acid were assessed. Secondary analyses were restricted to children with baseline CFA who completed 3-month treatment (n = 66, 10.5 ± 3.0 yrs, 40% female). Subjects were divided into two groups at baseline: those with lower CFA (≤87.8%, median) and higher CFA (above median). RESULTS: In those with lower baseline CFA, 3-month LXS treatment improved CFA significantly (8.7%, from 77.4 to 86.0%, P < 0.01), with a significant drop in stool fat loss (−6.6 g/24 hours) and no change in dietary fat intake. This was accompanied by significantly increased (P < 0.01) linoleic acid (434 nmol/L, 19% increase) and α-linolenic acid (25 nmol/L, 53% increase). Both weight and BMI Z scores increased ≥0.16 (P < 0.01). With placebo treatment, CFA did not change (72.5 to 71.1%), nor did EFA status, and growth status improved less (≤0.14, P < 0.05). For subjects with higher CFA at baseline, CFA did not change (92.1 to 90.1%) with either treatment, although EFA and growth status improved somewhat, with greater improvement evident in the LXS group. CONCLUSIONS: Subjects with CF and PI at higher risk for fat malabsorption had a dramatic improvement in CFA with LXS treatment, accompanied by improved EFA and growth status. This suggests that LXS may help those with CF and other pancreatic diagnoses in need of optimizing nutritional status and avoiding unintentional weight loss. FUNDING SOURCES: Supported by NIH.